Enhancing healthy eating patterns among Hong Kong young adults. (29th March 2019) - Kwok, Sin Tung; Capra, Sandra; Leveritt, Michael
Abstract: Every year, the majority of Hong Kong young adults who graduate from secondary school progress onto tertiary education. Poor eating patterns among young adults could lead to long-term health implications associated with overweight and obesity. Using the socio-ecological model as a theoretical framework, this paper reviews the current food-related policies in Hong Kong and proposes a comprehensive policy approach relevant to a variety of organizational contexts that has the potential to support positive eating patterns among young adults by enhancing the local food environment. Hong Kong has an unusual food supply in that more than 95% of food is imported, making it vulnerable to food insecurity. Education interventions commonly conducted in Hong Kong are unlikely to be helpful because young adults acquire nutrition-related knowledge when they attend secondary school. There is a need to change the food environment in Hong Kong so that young adults can easily translate their nutrition knowledge into making healthy food choices. Policy approaches might be among the most effective strategies for bringing positive changes in eating patterns because they have the potential to directly influence the food environment and context where an individual lives. A comprehensive suite of approaches that fill the policy gaps, remove barriers of healthy food consumption and create more healthy food choices is required to improve diet and health.